Opportunities, Challenges, and Strategies for Scalable Deposition of Metal Halide Perovskite Solar Cells and Modules - Azam Khorasani; Fateme Mohamadkhani; Maziar Marandi; Huiming Luo; Mojtaba Abdi‐Jalebi (Advanced Energy & Sustainability Research, 2024)
Hybrid organic‐inorganic perovskite solar cells (PSCs) have rapidly advanced in the new generation of photovoltaic devices. As the demand for energy continues to grow, the pursuit of more stable, highly efficient, and cost‐effective solar cells has intensified in both academic research and the industry. Consequently, the development of scalable fabrication techniques that yield a uniform and dense perovskite absorber layer with optimal crystallization plays a crucial role to enhance stability and higher efficiency of perovskite solar modules. This review provides a comprehensive summary of recent advancements, comparison, and future prospects of scalable deposition techniques for perovskite photovoltaics. We discuss various techniques, including solution‐based and physical methods such as blade coating, inkjet printing (IJP), screen printing, slot‐die coating, physical vapor deposition, and spray coating that have been employed for fabrication of perovskite modules. The advantages and challenges associated with these techniques, such as contactless and maskless deposition, scalability, and compatibility with roll‐to‐roll processes, have been thoroughly examined. Finally, the integration of multiple subcells in perovskite solar modules is explored using different scalable deposition techniques.